In schools, In community’ – implementing a university-school partnership at the University of Cape Town - Silbert, Patti (South African Journal of Higher Education, 2016)
The purpose of this paper is twofold: first, it describes the University of Cape Town’s Schools Improvement Initiative (SII) - a university-school partnership implemented in six schools in the Western Cape township of Khayelitsha. The second purpose is to report on the methodology of the case-study as used during the initial stage of intervention. Working in collaboration with faculties and groupings within the university; with education-related organisations in the community, and with the Metropole East Education District, the SII aims to bring about systemic school improvement in its partner schools. Through purposeful collaboration, the SII focuses its interventions on both the professional development of teachers and the organisational development of the school. Underpinning the SII’s work is a context specific approach, and it is through the methodology of the case-study that this is achieved. The case-study is used as an initiatior of dialogue and a preliminary ‘step to action’ (Adelman et al 1980 quoted in Cohen, Manion and Morrison 2009, 256). Accurately generated data from the case-study, that is openly shared with the participants, can be a powerful way to generate trust and collaboration, and engage all stakeholders in school improvement initiatives.